1976
DOI: 10.1002/pssa.2210380118
|View full text |Cite
|
Sign up to set email alerts
|

Surface ionic conductivity, lattice disorder, and space charge region in thin silver bromide layers

Abstract: Carefully controlled conditions of evaporation allow the preparation of epitaxial layers of pure AgBr. The temperature dependence of the conductivity of layers with varying thickness is measured. This in principle makes possible the splitting of the conductance into surface and bulk components. The bulk conductivity of the layers is found to be practically identical with that of pure large single crystals of AgBr, which until now has not been observed. For the first time considerable surface conductance is dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1977
1977
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 14 publications
(6 reference statements)
3
10
0
Order By: Relevance
“…Besides, using a probe of electrolytically sharpened silver point, it was found that the voltage varied linearly between the electrodes. Using Ohmic contacts, the values of the conductance obtained here f row dc measurements are similar to those from ac short pulses as described in [14]. Thus it can he concluded that a t the specified conditions the flow of charge is connected with nearly reversible electrode processes a t a negligible electrode polarization.…”
Section: Methodssupporting
confidence: 72%
See 2 more Smart Citations
“…Besides, using a probe of electrolytically sharpened silver point, it was found that the voltage varied linearly between the electrodes. Using Ohmic contacts, the values of the conductance obtained here f row dc measurements are similar to those from ac short pulses as described in [14]. Thus it can he concluded that a t the specified conditions the flow of charge is connected with nearly reversible electrode processes a t a negligible electrode polarization.…”
Section: Methodssupporting
confidence: 72%
“…First, etching substantially decreases the density of surface states which in accordance with theoretical expectations [27] leads to a decrease in the surface potential. A comparison of the density of negatively charged surface states 1.4 x 1013 cn1-2 found in [14] corresponding to the value evaluated in the present work indicates a decrease by two orders of magnitude. Second, the enhanced concentration of majority carriers in the non-stoichiometric material studied involves in turn a reduced SC region, hence a lower surface potential.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…[11] and [12] are used. Such a variation of densities may have a decisive influence on the conductivity of a thin crystal layer (12)(13)(14)(15)(16)20). The value of q~ for a particular interface is not known.…”
Section: Space Charge In a Passive Layermentioning
confidence: 99%
“…The unexpected results of measurements have been explained by morphology and the polycrystalline structure of the layer (8,9). The conductivity of such layers is strongly affected by the type of parent substrate (12)(13)(14), or by the electrolyte into which the layer is immersed (15,16), i.e., the mobile carrier density is essentially influenced by the interface between the crystal and the surrounding medium. This paper shows that the electrical properties of the passive layer can be explained by using results obtained in the field of solid-state batteries and thin crystal layers, e.g., silver and alkali halides.…”
mentioning
confidence: 99%